2020
DOI: 10.1182/blood.2019001576
|View full text |Cite
|
Sign up to set email alerts
|

Salt-inducible kinase inhibition suppresses acute myeloid leukemia progression in vivo

Abstract: Transcription factors are important drivers in acute myeloid leukemia (AML), but they are notoriously difficult to target. The authors demonstrate that inhibition of salt-inducible kinase (SIK3) inhibits AML cell proliferation in cells dependent on the transcription factor MEF2C, identifying a small molecule that can disrupt a leukemogenic transcription factor pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 72 publications
4
37
1
Order By: Relevance
“…156 It was also reported that a single point mutation of SIK3 (T142Q) or the inactivation of HDAC4 were enough to acquire the resistance to the YKL-05-099 treatment. 156 MRT-199665 is developed as an effective, ATP competitive, selective MARK/SIK/AMPK inhibitor. 8 MRT-199665 inhibits SIKmediated CRTC3 phosphorylation to increase LPS-stimulated IL-10 production and inhibit the secretion of proinflammatory cytokines, such as IL-6, IL-12, and TNFα in macrophages.…”
Section: Potential Inhibitors Targeting Siksmentioning
confidence: 99%
See 3 more Smart Citations
“…156 It was also reported that a single point mutation of SIK3 (T142Q) or the inactivation of HDAC4 were enough to acquire the resistance to the YKL-05-099 treatment. 156 MRT-199665 is developed as an effective, ATP competitive, selective MARK/SIK/AMPK inhibitor. 8 MRT-199665 inhibits SIKmediated CRTC3 phosphorylation to increase LPS-stimulated IL-10 production and inhibit the secretion of proinflammatory cytokines, such as IL-6, IL-12, and TNFα in macrophages.…”
Section: Potential Inhibitors Targeting Siksmentioning
confidence: 99%
“…160,161 Crenolanib has been found to have a strong nontargeting effect on SIK (IC 50 in vivo for SIK2 is 16 nM, for SIK3 is 2 nM), and shows good tolerance in human patients. 156 Staurosporine is likely to inhibit both SIK1 and SIK2 functions, and further considered as a nonselective kinase inhibitor at high concentrations to repress many kinases, including PKC, CaMK. 162,163 Staurosporine also increases CRTC2 abundance in nucleus and triggers CRH transcription in 4B cells by repressing SIKs.…”
Section: Potential Inhibitors Targeting Siksmentioning
confidence: 99%
See 2 more Smart Citations
“…We tested small molecule drugs targeting the ETS-factors ELK3, or ERG and FLI1 in dexamethasone resistant E/R+ REH cells and found reduced cell viability with sub-micromolar concentration. Inhibitors abrogating FLI1, MEF2C, ELK3, or SP4 activation have been previously shown to have efficacy in different cancers [94][95][96][97][98][99]. Moreover, the small molecule ERG/FLI1 inhibitor tested here has entered a phase 1 study in Ewing sarcoma [100].…”
Section: Single Cell Profiling Techniques Have Challenged How We Defimentioning
confidence: 99%